Fabrication of Chitosan Nanoparticles with Aggregation‐Induced Emission Characteristics and Their Applications in Long‐Term Live Cell Imaging. Issue 9 (11th February 2013) - Li, Min; Hong, Yuning; Wang, Zhengke; Chen, Sijie; Gao, Meng; Kwok, Ryan T. K.; Qin, Wei; Lam, Jacky W. Y.; Zheng, Qichang; Tang, Ben Zhong; Tang, B. Z.; Liu, B.
Abstract Chitosan with tetraphenylethene pendants (TPE‐CS) are synthesized by reaction between amine and isothiocyanate groups of chitosan and tetraphenylethene (TPE), respectively. Nanoparticles of TPE‐CS (TPE‐CS NPs) are fabricated by ionic gelation method. The NPs are uniform in size, spherical in shape, monodispersed, and positive in surface charge. The suspension of TPE‐CS NPs emits strong blue fluorescence under photoexcitation due to the aggregation‐induced emission characteristics of the TPE moieties. The NPs can be internalized into cytoplasm through endocytosis pathway and retain inside the live cells to image the cells. Cytotoxicity assay reveals that TPE‐CS NPs are cytocompatible and thus can be used for long‐term live cell imaging.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>